Systems change for the commons - Farooqui, Usmaan; Ratner, Blake D.; Rao, Jagdeesh; Chaturvedi, Rahul; Priyadarshini, Pratiti (Stanford University, 2021)
Instead of quick technical fixes, protecting India's 200 million acres of community lands means building platforms to ensure that different stakeholders act systematically, intentionally, and inclusively, and begins with the local and building from the ground up.